The development of the maintenance operations safety survey: challenges in transferring a predictive safety tool from flight operations to aircraft maintenance - Langer, Marie; Braithwaite, Graham (International Society of Air Safety Investigators, 2012)
Predicting human behaviour and managing human error is arguably the greatest challenge facing the aviation industry today (Shappell and Wiegmann, 2009). In order to gain a better understanding of human behaviour and overall organizational safety performance, the industry is moving towards monitoring of normal operations (Helmreich et al., 2003). One of the key advantages is the learning opportunity without the negative consequences and associated costs of an incident or accident. Predictive tools such as the Line Operations Safety Audit (LOSA) provide objective information of routine operational performance, complement existing safety data collection programs and are endorsed by the International Civil Aviation Organization (ICAO).